International Perspectives on Cyberbullying Prevalence, Risk Factors and Interventions (Palgrave Studies in Cybercrime and Cybersecurity, 2018)
This book brings together an international group of experts to present the latest psychosocial and developmental criminological research on cyberbullying, cybervictimization and intervention. With contributions from a wide range of European countries, including Cyprus, Greece, Ireland, Italy, France, Hungary, Spain, and the United Kingdom, as well as from Canada and the USA, this authoritative volume explores the nature, risk factors, and prevalence of cyberbullying among children and adolescents. A particularly original focus is directed towards the Tabby project (Threat Assessment of online Bullying Behaviour among Youngsters), an intervention programme based on the threat and risk assessment approach which seeks to prevent the occurrence of violence and its recidivism. Presenting cutting-edge research on developmental criminology and legal psychology, International Perspectives on Cyberbullying is a comprehensive resource for practitioners, teachers, parents, and researchers, as well as scholars of criminology, psychology, and education. .